Українська історична поезія ХVII-XVIII ст. як феномен "козацького бароко" - Семенюк, Лариса; Semeniuk, Larysa (Східноєвропейський національний університет імені Лесі Українки, 2015)
Українську барокову історичну поезію розглянуто з феноменологічного погляду, як відображення художньої свідомості козацької суспільної верстви. Як художній текст, феномен художньої свідомості, ця поезія підносить козацько- лицарські ідеали, утверджує демократичні настрої в козацькому середовищі, хоч і не позбавлена мілітарних настроїв, загалом не властивих українському козацтву.Ukrainian baroque historical poetry with a phenomenological perspective is considered in this article as a reflection of artistic consciousness of Cossack social stratum. It was the “bearer of a new artistic taste.” In the interpretation of Ukrainian authors Cossacks appears as a phenomenon of social and cultural life of Baroque. The ethnotype of man-Cossack, which appears in historical texts of ancient poetry, is a bearer of knightly virtues. He is ready to serve high ideas and stands in defense of their faith and community. He has a peculiar sense of responsibility but at the same time he has a destructive character. It harms its national interests. Ukrainian historical poetry as the text of art, the phenomenon of artistic consciousness elevates Cossack chivalry ideals. It strengthens democratic sentiment in the Cossack environment, though it isn’t devoid of military sentiments which are generally inappropriate for Ukrainian Cossacks. It represents Baroque features within the Cossack culture with its penchant for universal thinking, dynamism, contrast and high emotion.
Ukrainian Historical Poetry of 17−18th Centuries as the Phenomenon of “Cossack Baroque”
Keywords: козацтво; «козацьке бароко»; козацька свідомість; історична поезія; К. Сакович; І. Мазепа; П. Орлик; Cossacks; “Cossack Baroque”; Cossack consciousness; historical poetry; K. Sakovych; I. Mazepa; P. Orlyk